Case Report: Modified Arthroplasty and Cement Augmentation for Proximal Humerus Osteosarcoma Reconstruction—Short-Term Functional Outcomes - Muhamad Naseh Sajadi Budi; Muhammad Rifki Faiz; Masganjar Nugraha (The International Journal of Medical Science and Health Research, 2026)
Introduction : Reconstruction of the proximal humerus after wide tumor excision presents a significant surgical challenge. This case report evaluates the short-term functional outcomes of a modified arthroplasty technique reinforced with bone cement and internal fixation for proximal humerus osteosarcoma. Case Presentation: A 25-year-old male presented with a progressively painful and enlarging mass on his left shoulder over eight months. Imaging and histopathology confirmed high-grade osteosarcoma of the left proximal humerus, Enneking classification IIB. The patient underwent limb-salvage surgery starting with a wide en bloc tumor excision. Reconstruction was performed using a modified shoulder arthroplasty technique: a size-24 shoulder stem prosthesis was implanted and augmented with polymethyl methacrylate (PMMA) bone cement for enhanced stability. To provide additional mechanical reinforcement and secure anchor points for soft-tissue reattachment, a 4.5 narrow locking 9-hole plate and screws were secured to the construct. The patient subsequently completed six cycles of adjuvant chemotherapy. Results: At the 12-month follow-up, the patient achieved an excellent Musculoskeletal Tumor Society (MSTS) score of 80%. Clinical evaluation demonstrated good active range of motion with no signs of local recurrence or distant metastasis. Discussion: The use of PMMA cement provided immediate rigid fixation for early mobilization, while the supplemental locking plate acted as a critical anchor for reattaching the joint capsule and remaining musculature. Compared to conventional silver-coated or standard modular megaprostheses, which often face challenges regarding soft-tissue integration and high costs in developing regions, this modified approach offers a more accessible and biomechanically stable alternative for restoring shoulder mechanics. This modification effectively addresses the common clinical problem of postoperative shoulder instability caused by the extensive loss of dynamic stabilizers during oncological resection. Conclusion : The combination of cemented tumor arthroplasty with supplemental plate fixation is a feasible and effective strategy, providing immediate mechanical stability and reliable soft-tissue reattachment for complex proximal humerus reconstruction.